Kinetic-Monte-Carlo-Based Parallel Evolution Simulation Algorithm of Dust Particles - Xiaomei Hu; Zhifeng Xu; Hongxia Cai; Junjun Hu (Journal of Applied Mathematics)
The evolution simulation of dust particles provides an important way to analyze the impact of dust on the environment. KMC-based parallel algorithm is proposed to simulate the evolution of dust particles. In the parallel evolution simulation algorithm of dust particles, data distribution way and communication optimizing strategy are raised to balance the load of every process and reduce the communication expense among processes. The experimental results show that the simulation of diffusion, sediment, and resuspension of dust particles in virtual campus is realized and the simulation time is shortened by parallel algorithm, which makes up for the shortage of serial computing and makes the simulation of large-scale virtual environment possible.